Effects of Ultrasonic Stimulation on Resistance to Sheath Blight (Rhizoctonia solani) in Rice - Zhang, Yungang; Wang, Bochu; Zhang, Xiaogang; Shi, Lanchun; Zhu, Liqing (Asian Journal of Chemistry, 2012)
Plant pathogen can cause a series of defensive responses, such as changes of defense enzymes in plant. The effects of ultrasound on resistance to sheath blight in rice (Tetep and Wanhui 88) were examined in the present study. The results showed that ultrasound can increase germination capacity and the content of chlorophyll and activities of superoxide dismutase (SOD) and polyphenol oxidase (PPO), decrease disease index and the content of malondialdehyde (MDA) in response to Rhizoctonia solani in rice. It was concluded that ultrasound may enhance the resistance of rice against sheath blight through improving the activity of some defence related metabolisms.